Dakwah Salafi di Tanah Pakpak: Analisis Konflik dan Transformasi Sosial Keagamaan di Desa Silima Kuta, Pakpak Barat, Sumatera Utara - Syaki Padang; Aulia Kamal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article discusses how the conflict between the Pakpak community and Salafi groups has led to changes in social and religious practices in Desa Silima Kuta. The research is a qualitative-descriptive study where data were collected through field research using in-depth interviews, observation, and documentation. The data were then analyzed descriptively, using conflict and social change theories as the analytical framework. The study finds two main points: First, conflicts based on ideological differences have driven social and religious changes through two factors: (1) the hegemonic competition between Salafi groups and local religious leaders, with both vying for influence in the community; (2) a sense of threat among the Pakpak people, who fear that Salafi teachings might alter their religious traditions, thereby increasing the community’s enthusiasm and participation in religious activities in Desa Silima Kuta. Second, the forms of social and religious changes observed include: changes in practices of dhikr (remembrance of Allah), communal prayers after congregational prayers, tahlilan (commemorative prayers for the deceased), yasinan (recitation of Surah Yasin), changes in attire during worship, and decreased participation in major Islamic celebrations such as Maulid and Isra' Mi'raj.